Kekerasan dalam Rumah Tangga Perspektif Tafsir Tematik - Sabari Sabari; Rosmini; Sohrah (CV Global Research Publication, 2026)
Domestic violence (DV) is a social problem that continues to increase and has serious impacts on women, children, and the structure of modern families. In the context of Islamic studies, several Qur’anic verses such as Q.S. An-Nisā’ 34, Q.S. Al-Baqarah 231–232, Q.S. An-Nisā’ 19, and Q.S. At-Taḥrīm 6 are often misunderstood as justifications for acts of domestic violence. This study examines these verses using the thematic exegesis method through the stages of verse arrangement, contextual analysis (asbāb al-nuzūl and munāsabah), concept integration, and a comprehensive study that combines all relevant scriptural texts. The results of the analysis show that these verses do not legitimize violence, but rather function as corrective and preventive instruments to protect families from Jahiliyyah practices characterized by gender inequality. The principle of tadarruj in Islamic law plays a role in gradually restructuring social order from a culture of violence toward more just and civilized family relations. Supporting evidence from the Prophet’s hadiths and the narrations of the Companions further emphasizes that Islam rejects harmful physical abuse and prioritizes conflict resolution based on dialogue, moral education, and protection. Therefore, a thematic understanding of these verses produces a relevant and contextual perspective for preventing domestic violence in contemporary society.